Strengthen the weakest link - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Building businesses with small producers By S Kapila & D Mead, ITDG Publications, 2002. 137 pp. ISBN 1853394947 GBP 14.95 Euro 23.45